Death by Stimulation of the Left Vagus Nerve in a Case of Neck Grasping in a Healthy Young Man (Medico Legal Update, 2021)
Fatal neck pressure due to manual strangulation is a relatively common event. Sudden deaths that occur inthe first seconds of pressure are attributed to effects of the nerve. According to leading authors, the processoccurs through a reflex arc where the afferent (sensory) nerve impulses emerge in the carotid complex of thenerve endings, but not in the vagus trunk itself.On the contrary, we describe one such fatality. The body of a man in his early twenties came to attention inour Institute. According to testimonies and investigations, the victim had a domestic fight with his brother.After a verbal altercation, the victim was grabbed by the neck and immediately fell dead. During the externalexamination, only two small finger-nail superficial abrasions were found in the left cervical region. No othersigns of violence were detected. The dissection of the neck only revealed a perineural hematoma in theleft vagus trunk in the cervical tract. The cause of death was attributed to neurally mediated cardiac arrestinduced by direct left vagus nerve compression.